Making urban Asia air cleaner. - Marsden, Emma ([Manila] Asian Development Bank, 2019)
More than 90% of cities in Asia are experiencing unhealthy levels of air pollution, adversely affecting the environment, health, and quality of life in the region. The brief presents data from a study on Chengdu, Kathmandu, Metro Manila, and Xiangtan that identifies risk factors to the population and the common challenges that Asian cities face. It recommends air quality management solutions that address these risks and challenges and that will help make cities in the region more livable.
Keywords: Urbanization -- Environmental aspects; Sustainable development; Environmental impact analysis; Electronic book